Pokój Boży w pismach natchnionych Starego Testamentu - Homerski, Józef (The Biblical Annals, 2017)
The „peace of God” does not occur in the books of the Old Testament. Though the idea of the peace of God is very vivid in them. One should not look for it in the semantic field of the word „shalom” but in the context of those hagiographic texts, especially those written by prophets, in which there appears the word „shalom” and in those oracles which deal with the idea of peace, though the very word „peace” does not turn up. The peace of God is God’s gift which man cannot give to himself or work out. This means those spiritual goods thanks to which man (both as an individual and society) is in total harmony with God and creature.